Local Wisdom and STEM in Science Education to Support SDG-4: A Systematic Review - Rosyidah, Fitrotin; Susantini, Endang; Yuliani, Yuliani; Nisa', Khoirun (Jurnal Pendidikan IPA Indonesia, 2025)
The integration of local wisdom into science learning is a global pedagogical trend that leads to the Sustainable Development Goals (SDGs 4). Local wisdom serves to make scientific concepts contextual, meaningful, and culturally relevant for students. The challenge of contextual implementation can be addressed through interdisciplinary approaches such as STEM (Science, Technology, Engineering, and Mathematics), which serve as a bridge between local wisdom and education. This systematic literature review (SLR) modified with Bibliometric Analysis aims to map the global research landscape on the integration of local wisdom and STEM in formal science education from 2014 to 2024. A total of 155 articles indexed in the Scopus database were analyzed using Bibliometric analysis tools, including VOSviewer, Microsoft Excel, and Datawrapper. The results show an increase in publications post-pandemic, driven by the urgency of advancing SDG 4 and the need for adaptive learning innovation. Geographically, research is concentrated in the United States, Indonesia, and South Africa, with global collaborations indicating this issue as a transnational agenda. An in-depth review of 21 inclusive articles reveals a predominance of qualitative-exploratory approaches. Subject distribution indicates a strong focus on General Science Education, Environment/Ecology, and Biology. Furthermore, research is predominantly focused on higher education and junior high school levels, while high school and elementary school levels remain underrepresented. The study's conclusions highlight the central role of STEM as a bridge in integrating local wisdom.